Belgium : 2021 Article IV Consultation -Press Release; Staff Report; and Statement by the Executive Director for Belgium. (IMF Staff Country Reports; Country Report ;, 2021)
Belgium was hit hard early by Covid-19, but a timely, strong, and sustained health and economic policy response helped cushion impacts. A coalition government took office in October 2020, giving greater policy clarity and rightly prioritizing the Covid-19 crisis. A highly-effective vaccine rollout has facilitated reopening and recovery.